"let it be": Őszikék as the cycle of humorous repetition - Z. Kovács, Zoltán (MEDIATON OF HUNGARIAN LANGUAGE CULTURE, 2019)
The study deals with the interpretation questions of the Őszikék cycle written by János Arany. It examines what kind of relationship these late poems have with the earlier lyre of Arany from the point of view of the interpretation of the topics, poetry and the poet’s position. According to its conclusion, Őszikék, contrary to their innovative  role held in the public consciousness of literary history approaching them both from poetic self-definition and Arany’s humour, are the integral continuation of the lyre of the 1850ies.
Keywords: János Arany; Őszikék; humor; positions of the poet